Effect of electroacupuncture on the mRNA and protein expression of Rho-A and Rho-associated kinase II in spinal cord injury rats - You-jiang Min; Li-li-qiang Ding; Li-hong Cheng; Wei-ping Xiao; Xing-wei He; Hui Zhang; Zhi-yun Min; Jia Pei (Neural Regeneration Research, 2017)
Electroacupuncture is beneficial for the recovery of spinal cord injury, but the underlying mechanism is unclear. The Rho/Rho-associated kinase (ROCK) signaling pathway regulates the actin cytoskeleton by controlling the adhesive and migratory behaviors of cells that could inhibit neurite regrowth after neural injury and consequently hinder the recovery from spinal cord injury. Therefore, we hypothesized electroacupuncture could affect the Rho/ROCK signaling pathway to promote the recovery of spinal cord injury. In our experiments, the spinal cord injury in adult Sprague-Dawley rats was caused by an impact device. Those rats were subjected to electroacupuncture at Yaoyangguan (GV3), Dazhui (GV14), Zusanli (ST36) and Ciliao (BL32) and/or monosialoganglioside treatment. Behavioral scores revealed that the hindlimb motor functions improved with those treatments. Real-time quantitative polymerase chain reaction, fluorescence in situ hybridization and western blot assay showed that electroacupuncture suppressed the mRNA and protein expression of Rho-A and Rho-associated kinase II (ROCKII) of injured spinal cord. Although monosialoganglioside promoted the recovery of hindlimb motor function, monosialoganglioside did not affect the expression of Rho-A and ROCKII. However, electroacupuncture combined with monosialoganglioside did not further improve the motor function or suppress the expression of Rho-A and ROCKII. Our data suggested that the electroacupuncture could specifically inhibit the activation of the Rho/ROCK signaling pathway thus partially contributing to the repair of injured spinal cord. Monosialoganglioside could promote the motor function but did not suppress expression of RhoA and ROCKII. There was no synergistic effect of electroacupuncture combined with monosialoganglioside.